1996
DOI: 10.1097/00006842-199603000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Analgesic Consumption for Postoperative Pain

Abstract: Ethnicity exerts a powerful impact on medical care. We cannot determine from our data whether these differences stem from differences in pain behavior of the patients or differences in medical staff's perception and treatment of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
1
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 18 publications
0
87
1
5
Order By: Relevance
“…Comparable racial/ethnic inequalities in receipt of opioid analgesics for acute pain, but not nonopioid analgesics, have been observed for different presenting complaints, including musculoskeletal pain and back pain [42,43,55]. Examination of the literature concerning postoperative care shows, irrespective of study design, surgical procedure investigated, patient age, or whether or not patient-controlled analgesia was administered, whites received higher doses of opioid analgesics than African Americans, non-Hispanic whites, or Asian Americans [62,72,73] or were more likely to receive analgesic medications adequate to their pain level [64]. More distressing, Jimenez et al [47] reported differences in perioperative analgesic prescribing between Latino and white children who had a tonsillectomy/adenoidectomy.…”
Section: Acute Nonmalignant Painmentioning
confidence: 99%
“…Comparable racial/ethnic inequalities in receipt of opioid analgesics for acute pain, but not nonopioid analgesics, have been observed for different presenting complaints, including musculoskeletal pain and back pain [42,43,55]. Examination of the literature concerning postoperative care shows, irrespective of study design, surgical procedure investigated, patient age, or whether or not patient-controlled analgesia was administered, whites received higher doses of opioid analgesics than African Americans, non-Hispanic whites, or Asian Americans [62,72,73] or were more likely to receive analgesic medications adequate to their pain level [64]. More distressing, Jimenez et al [47] reported differences in perioperative analgesic prescribing between Latino and white children who had a tonsillectomy/adenoidectomy.…”
Section: Acute Nonmalignant Painmentioning
confidence: 99%
“…through the use of a cold-pressor task; Nayak, Shiflett, Eshun, & Levine, 2000) and clinical settings (e.g. post-operative pain; Ng, Dimsdale, Shragg, & Deutsch, 1996). Second, and potentially offering an explanation for at least some of the above cultural differences, social modelling directly affects individuals' pain responses.…”
Section: The Social-psychological Contribution To Pain Responsesmentioning
confidence: 99%
“…Similarly, ethnic disparities in analgesic administration were observed in patients recovering from open reduction and internal fixation procedures. In a study, nonHispanic whites received more morphine equivalent medication than latino or black patients [18]. Another recent study supports a culturally-mediated basis for differences in pain perception or reporting [19].…”
Section: Discussionmentioning
confidence: 92%